Finite Element Analysis and Structure Improvement of Truck Driving Axle Housing - Wu Xiaoquan (Jixie chuandong)
Aming at verifying the working characteristics of a truck driving axle housing,the strength of rear axle is analyzed based on the finite element method,the analysis result shows that maximum stress beyond material tensile strength when it was 6 time full loading. The maximum stress is 549.0 MPa by increasing chamfer and increasing 10 mm at vertical distance,it is reduced by 10%. The fatigue life of front axle is predicted based the method of S-N,the result shows that the minimum life is 1.57×106,it exceeds the national standard of 8×105 cycles. The first free modal frequency and first constraint modal frequency are 101.5 Hz and125.9 Hz after optimization. They are outside the range of excitation frequency of engine idle speed,and the resonance would be effectively avoided. The maximum displacement of per meter is 1.097 mm/m,it less than1.5 mm/m of national standards,so its optimization meet the requirement of stiffness,modal,strength and fatigue.